Cellulose acetate membrane preparation for the separation of small molecules - Taladua, Gladys Paz R. (Animo Repository, 1995)
The phase inversion process for the production of ultrafiltration membranes utilizing pure cellulose acetate polymers of different concentrations was investigated. The membranes rejection coefficients and separation efficiency for more effective separation of glucose was evaluated by the use of surfactants. Membranes of higher polymer concentration exhibited higher rejection coefficients with high separation efficiency of glucose. The effects of parameters fouling, concentration polarization, membrane compaction contributed to a decrease in water fluxes of membranes produced. The best polymer concentration that gave satisfactory membrane characteristics and recovery of glucose was observed at 15.00 percent using cationic surfactants.